Microwave radiation associated with lightning initiation events of negative cloud-to-ground flashes - Al-Kahtani, Ammar Ahmed; Ahmad, Mohd Riduan; Mohammad Sabri, Muhammad Haziq; Shamsul Baharin, Shamsul Ammar; Lu, Gaopeng; Kawasaki, Zen; Cooray, Vernon (MDPI, 2022)
In this paper, we examined the initiation events of ten negative cloud-to-ground (CG) flashes detected close to measurement stations on 12 November (CG-1 to CG-5) and 24 November (CG-6 to CG-10), 2019. All CG flashes were accompanied by microwave and very-high frequency (VHF) radiation pulses. We recorded all the CG flashes from two measurement stations (ST1 and ST2), which are separated by 13.3 km and consist of fast and slow antenna (FA and SA) sensors, a magnetic field (B-field) sensor, a VHF sensor (60 MHz), and a microwave sensor (~1 GHz). The key finding is that all of the microwave radiation pulses detected before the onset of initial electric field changes (IECs) preceded all VHF radiation pulses with an average lead time of 1.53 µs, ranging between 0.3 and 3.0 µs (for all CG flashes within reversal distance). A total of 50%, 17%, and 33% CG flashes were initiated by a single radiation pulse, two radiation pulses, and three radiation pulses, respectively, and were followed by IECs. Some VHF pulses are classified as short VHF radiation pulses (pulse duration less than 0.5 µs). The average duration from the first microwave and VHF pulses to the onset of IECs were 53.4 µs and 32.78 µs, respectively. The VHF radiation pulses detected before the IECs are suggested to be emitted by short-length positive streamers. Because the microwave radiation pulses were detected earlier (average lead time of 1.53 µs) than VHF radiation pulses, it is most likely that the microwave pulses were emitted by an electron avalanche process.